SELULITIS PRESEPTAL DAN ORBITAL - Hondrizal, Hondrizal; Ade Ariadi; Adji Mustiadji (Yayasan Nusantara Hasana Berdikari, 2025)
Preseptal cellulitis and orbital cellulitis are soft tissue infections surrounding the eye that may lead to serious complications if not properly managed. Preseptal cellulitis is confined to the tissues anterior to the orbital septum, whereas orbital cellulitis involves structures posterior to the septum and carries a higher risk of visual impairment and intracranial complications. These conditions are commonly caused by the spread of infection from the paranasal sinuses, trauma, insect bites, or local eyelid infections. Clinically, preseptal cellulitis presents with eyelid edema and erythema without impairment of ocular motility or visual acuity, while orbital cellulitis is characterized by more severe symptoms such as pain with eye movement, proptosis, ophthalmoplegia, and decreased visual acuity. Diagnosis is based on clinical evaluation and supported by imaging studies, particularly orbital computed tomography (CT) scans, to differentiate between the two conditions. Management of preseptal cellulitis typically involves oral antibiotic therapy, whereas orbital cellulitis requires intravenous antibiotics, close monitoring, and possibly surgical intervention. Early and accurate diagnosis followed by prompt treatment is essential to prevent serious complications and preserve visual function.